O outro lado da evasão no ensino superior: a persistência acadêmica dos discentes no caminho para a graduação - Rocha, Leandro Sarubbi de Carvalho (2020)
This study aimed investigate successful cases of students that attend in Accounting Sciences course in two higher education institutions (IES), one public and one private, located in the city of Fortaleza - CE, whith the purpose to identify the factors of the academic persistence that contributed to the subjects success in overcoming difficulties and fulfilling the dream, common to many students, of graduating. With a qualitative approach, based on psychological, relational, sociological, economic and organizational factors for academic persistence in higher education found in the studys of Himmel (2002) and Gómes (2015), complemented by the theories of the sociological explanation for the permanence or dropout in higher education by Spady (1970) and Tinto (1975) and by studies developed on academic engagement, the research aimed to capture conceptions, perspectives, reports, speeches and experiences within the university environment that express the students academic persistence from a perspective that, many times, are not demonstrated significantly in numbers. In this aspect, the research had as main instrument for data collection the conduction of focus groups, separated by groups of students exclusive for each type of IES, public or private, using auxiliary techniques for contextualization and selection of subjects such as document analysis and the application of a questionnaire with the objective of exploring the personal and academic profiles of students and measuring the level of engagement of participants using the Utrecht Work Engagement Scale (UWES-S) tool. The results showed that psychological factors was related to the search for a better social condition, to the family support, the knowledge acquired in high school and for characteristics such as resilience that served as foundation to the subjects in overcoming the difficulties. As relational factors, the sharing of academic activities with colleagues, the technical quality of teachers and the emotional support received in the learning process were the most cited causes for promoting academic persistence. As for sociological, economic and organizational factors, it can be highlighted that support and organization for reconciling time between academic, professional and personal activities, access to transport, employment and income, mental health and alignment with the rules and IES policies were the points that most contributed to the subjects academic persistence.